Causes and Characteristics of Professional Mobility for Teachers in Morocco, Case of secondary School Teachers Who Have Chosen to Become Educational Guidance Counselors - Abderrazak Faiq; Brahim Darraj; Azzeddine Atibi; Mohamed Radid (Iraqi Journal of Science, 2021)
When it comes to changing one's profession after a several years of professional experience in a given field, It must be admitted that the person who adopts this approach is very persevering in the quest for self-realization. Thus, the search for improvement of the working environment and its conditions are often behind this type of choice. To try to understand this phenomenon of professional mobility, we conducted a study that concerning 1st cycle secondary school teachers who became guidance counselors and we focus on two parameters concerning this population: the causes that led them make this choice, and their socio-cultural characteristics (entry profiles). This information was collected via a questionary administered to all active guidance counselors. The results of this research led us to conclude a review of the flow of national education staff and to highlight the lack of professionals for certain subjects taught.